Establishing a welfare policy program for cargo drivers in the Rep. of Korea: A comparative analysis of cargo driver employees - Han, Sang Bae; Park, Min Jae (Transportation Research Interdisciplinary Perspectives, 2025)
Cargo transportation plays a vital role in national economic development, yet the welfare of cargo drivers has long been overlooked in South Korea. This study aims to evaluate and prioritize welfare policies for cargo drivers by applying the Analytical Hierarchy Process (AHP), drawing on expert opinions from drivers, industry practitioners, and policymakers. By examining financial, psychological, technical, and policy-related welfare factors, this study provides a structured understanding of the needs and expectations of key stakeholders. The findings reveal that financial factors—such as livelihood support and loan programs—are prioritized by drivers, while policy-related factors—such as cargo rate systems and consignment mechanisms—are more emphasized by industry workers and decision-makers. This divergence highlights the need for better alignment between welfare policy design and field-level needs. This study contributes to the transportation and logistics literature by offering a comprehensive framework for evaluating welfare priorities in the freight sector. It advances the application of AHP in public welfare decision-making and underscores the importance of multi-stakeholder engagement in policy formulation. The results are expected to guide the establishment of a sustainable and inclusive welfare system for cargo drivers, particularly as the industry transitions toward automation, eco-friendly transport, and digitalization.
Keywords: AHP; Cargo Drivers; Policy Alignment; Stakeholder Analysis; Sustainable Transport; Welfare Policy